A novel method to improve the osteogenesis capacity of hUCMSCs with dual‐directional pre‐induction under screened co‐culture conditions. (9th December 2019) - Rong, Qiong; Li, Shuyi; Zhou, Yang; Geng, Yuanming; Liu, Shangbin; Wu, Wanqiu; Forouzanfar, Tim; Wu, Gang; Zhang, Zhiyong; Zhou, Miao
Abstract: Objectives: Mesenchymal stem cells (MSCs) based therapy for bone regeneration has been regarded as a promising method in the clinic. However, hBMSCs with invasive harvesting process and undesirable proliferation rate hinder the extensive usage. HUCMSCs of easier access and excellent performances provide an alternative for the fabrication of tissue‐engineered bone construct. Evidence suggested the osteogenesis ability of hUCMSCs was weaker than that of hBMSCs. To address this issue, a co‐culture strategy of osteogenically and angiogenically induced hUCMSCs has been proposed since thorough vascularization facilitates the blood‐borne nutrition and oxygen to transport in the scaffold, synergistically expediting the process of ossification. Materials and methods: Herein, we used osteogenic‐ and angiogenic‐differentiated hUCMSCs for co‐culture in screened culture medium to elevate the osteogenic capacity with in vitro studies and finally coupled with 3D TCP scaffold to repair rat's critical‐sized calvarial bone defect. By dual‐directional induction, hUCMSCs could differentiate into osteoblasts and endothelial cells, respectively. To optimize the co‐culture condition, gradient ratios of dual‐directional differentiated hUCMSCs co‐cultured under different medium were studied to determine the appropriate condition. Results: It revealed that the osteogenic‐ and angiogenic‐induced hUCMSCs mixed with the ratio of 3:1 co‐cultured in the mixed medium of osteogenic induction medium to endothelial cell induction medium of 3:1 possessed more mineralization nodules. Similarly, ALP and osteogenesis/angiogenesis‐related genes expressions were relatively higher. Further evidence of bone defect repair with 3D printed TCP of 3:1 group exhibited better restoration outcomes. Conclusions: Our work demonstrated a favourable and convenient approach of dual‐directional differentiated hUCMSCs co‐culture to improve the osteogenesis, establishing a novel way to fabricate tissue‐engineered bone graft with 3D TCP for large bone defect augmentation.